COMIC MEDIA AS AN EFFORT TO IMPROVE KNOWLEDGE AND ATTITUDES ABOUT MENARCHE - Matin, Nur Sophia; Wittiarika , Ivon Diah; Faizah , Zakiyatul (Indonesian Midwifery and Health Sciences Journal, 2025)
Background: The age of menarche is getting younger, yet many elementary students are not prepared in terms of knowledge and attitudes. Comic media as an interactive educational method can increase understanding about menarche in a fun and easy-to-understand way. Objective: To analyze the effect of comic media on improving knowledge and attitudes about menarche in fifth-grade elementary school girls. Method: A quasi-experimental study with a pretest-posttest design in the treatment (comic) and control (lecture) groups using total sampling of 66 fifth-grade girls who had not experienced menarche. Data were analyzed using paired t-test and independent t-test. Results: There was a significant increase in knowledge in the comic group (p=0.000). Although not statistically significant, there was a positive increase in attitudes in the comic group compared to lectures. Conclusion: Comic media is effective in increasing knowledge and potentially improving the attitudes of elementary school girls regarding readiness for menarche.